Increased Production of Interleukin-4, Interleukin-10, and Granulocyte-Macrophage Colony-Stimulating Factor by Type 2 Diabetes' Mononuclear Cells Infected with Dengue Virus, but Not Increased Intracellular Viral Multiplication. (2nd September 2013) - Lee, Ing-Kit; Hsieh, Ching-Jung; Chen, Rong-Fu; Yang, Zih-Syuan; Wang, Lin; Chen, Chang-Mei; Liu, Chiung-Fen; Huang, Chung-Hao; Lin, Chun-Yu; Chen, Yen-Hsu; Yang, Kuender D; Liu, Jien-Wei
Abstract : It has been reported that diabetes mellitus (DM) was an epidemiologically identified risk factor for development of dengue hemorrhagic fever (DHF)/severe dengue in dengue virus (DENV) affected patients, and T helper 2 (Th2) cytokines such as interleukin-4 (IL-4) and IL-10 each plays an important role in the immunopathogenesis of DHF in studies involving general population. To better understand the relationship between these epidemiological and immunological findings, we performed an in vitro study evaluating the sequential immunological reactions and viral load in the DENV infected mononuclear cells of adults with type 2 DM (T2DM group, n = 33 ) and normal adults (control group, n = 29 ). We found in the T2DM group significantly higher IL-4 level on the first ( P = 0.049 ) and the third ( P = 0.022 ) postinfection days, while higher IL-10 ( P = 0.042 ) and granulocyte-macrophage colony-stimulating factor (GM-CSF) ( P = 0.009 ) were detected on the third postinfection day. No significant difference in DENV viral load between the cultured mononuclear cells from both groups was found on the first and third post-infection days. These data immunologically suggest that patients with T2DM are at higher risk for development of DHF/severe dengue and strengthen the previously epidemiologically identified role of DM being a predictive risk factor for progressing into DHF/severe dengue in DENV-affected patients.